ҲӘЗИРГИ ҚАРАҚАЛПАҚ ТИЛИНДЕ ҚОСПА ГӘПЛЕР ФОРМАСЫНДАҒЫ ПАРЦЕЛЛЯЦИЯ КОНСТРУКЦИЯЛАРЫ - Халмуратов, Т.Ж. (FAN va JAMIYAT, 2025)
The article is devoted to the study of partial complex constructions in the modern Karakalpak language.